2022
DOI: 10.1155/2022/3346648
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Application and Development of Mural Art in Urban Public Environment Landscape Design

Abstract: With the gradual improvement of social and economic levels, cities not only meet people’s basic living needs, but also have an artistic expression to a certain extent, and the public pays more attention to the beauty of the external environment. Landscapes in cities are settlement landscapes characterized by man-made landscapes, which are not only a cultural resource but also an ecological environment resource. Murals are also the first works of art of mankind. According to records, murals are the largest numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The history of urban arts can be traced back to the early days of human civilization, where artistic expressions emerged within the context of urban environments [5]. From the ancient cities of Mesopotamia and Egypt to the bustling metropolises of ancient Greece and Rome, urban spaces have served as platforms for creative endeavors.…”
Section: Historical Contextmentioning
confidence: 99%
“…The history of urban arts can be traced back to the early days of human civilization, where artistic expressions emerged within the context of urban environments [5]. From the ancient cities of Mesopotamia and Egypt to the bustling metropolises of ancient Greece and Rome, urban spaces have served as platforms for creative endeavors.…”
Section: Historical Contextmentioning
confidence: 99%
“…Administrators, engineers, and designers have attempted to dissipate the negative visual impact of these structures on the environment. Although some studies point out that retaining walls can achieve positive visual effects in urban streets and improve the scenic appearance [ 10 ], its effect is unclear in the mountains and valleys. Currently, there are two main types of retaining wall beautification: one is to apply flat murals to improve the single and rigid color composition and forms [ 11 ], and the other is to employ three-dimensional materials like stones, timbers, and ceramics to decorate the retaining walls [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%